PKM ISLAMIC KONSELING UNTUK MENGATASI NOMOPHOBIA PADA REMAJA DI SMAN 1 KUANTAN MUDIK LUBUK JAMBI - Alini Alini; Langen Nidhana Meisyalla (Universitas Pahlawan Tuanku Tambusai, 2022)
The activity of using a mobile phone is a habit that is seen as commonplace for many people. However, without realizing it, excessive intensity in interacting with mobile phones can certainly cause various impacts on users, such as nomophobia- no mobile phone phobia. Nomophobia is the anxiety that users feel when they are away from their mobile phone. nomophobia refers to the discomfort, anxiety, nervousness or sadness caused by not having anything to do with a cell phone. The form of discomfort, anxiety, anxiety, or sadness in nomophobia sufferers has exceeded reasonable limits and leads to addictive behavior. Nomophobia and smart-phone addiction disorder have many comorbid disorders, two or more disorders in individuals, such as anxiety and panic disorder. By implementing counseling as well as re-instilling religious values, the counselee will be able to reduce his addiction to smartphones, because nomophobia is a form of human being that is too concerned with worldly affairs. So that after the implementation of Islamic counseling, the counselee is aware of his relationship with God and begins to reduce his relationship with the smartphone. Keywords: Counseling, Nomophobia, Smartphone